Yablo's Paradox and ω-inconsistency - Ketland, J (2005)
It is argued that Yablo's Paradox is not strictly paradoxical, but rather 'ω-paradoxical'. Under a natural formalization, the list of Yablo sentences may be constructed using a diagonalization argument and can be shown to be ω-inconsistent, but nonetheless consistent. The derivation of an inconsistency requires a uniform fixed-point construction. Moreover, the truth-theoretic disquotational principle required is also uniform, rather than the local disquotational T-scheme. The theory with the local disquotation T-scheme applied to individual sentences from the Yablo list is also consistent. © Springer 2005.